2022
DOI: 10.1161/jaha.121.024214
|View full text |Cite
|
Sign up to set email alerts
|

Generalizability of the EAST‐AFNET 4 Trial: Assessing Outcomes of Early Rhythm‐Control Therapy in Patients With Atrial Fibrillation

Abstract: Background EAST‐AFNET 4 (Early Treatment of Atrial Fibrillation for Stroke Prevention Trial) demonstrated clinical benefit of early rhythm‐control therapy (ERC) in patients with new‐onset atrial fibrillation (AF) and concomitant cardiovascular conditions compared with current guideline‐based practice. This study aimed to evaluate the generalizability of EAST‐AFNET 4 in routine practice. Methods and Results Using a US administrative databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Larger prospective studies would be helpful in assessing large-scale changes in treatment patterns to thoroughly investigate the safety of therapies. Recently, an analysis of a US administrative database found approximately 3/4 of all patients with newly diagnosed AF would be eligible for early rhythm control, which is comparable with our findings 19…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Larger prospective studies would be helpful in assessing large-scale changes in treatment patterns to thoroughly investigate the safety of therapies. Recently, an analysis of a US administrative database found approximately 3/4 of all patients with newly diagnosed AF would be eligible for early rhythm control, which is comparable with our findings 19…”
Section: Discussionsupporting
confidence: 91%
“…Recently, an analysis of a US administrative database found approximately 3/4 of all patients with newly diagnosed AF would be eligible for early rhythm control, which is comparable with our findings. 19 Several factors could explain the low use of OAC in the UKB. For one, we capture a part of the whole population since we focused on optimal data quality and excluded those without Additionally, a recent study using a database of primary care data in the UK from 2008 to 2018 showed that OAC use in the UK was around 43% and only recently increased to 71.6%.…”
Section: Arrhythmias and Sudden Deathmentioning
confidence: 99%
“…By identifying sinus rhythm during the initial follow up as the major mediator of the effectiveness of rhythm control therapy, our analysis provides a physiological rationale for ERC in routine care. The safety of ERC has been replicated in several analyses of large record data sets in South Korea, 17 the USA, 5 and in the UK BioBank. 6 Consistent with our observation, randomization to the antiarrhythmic drug dronedarone was associated with reduced cardiovascular mortality and less ischaemic strokes (HR 0.66; 95% CI 0.45–0.96) in a subanalysis of the ATHENA trial (a placebo-controlled, double-blind, parallel arm trial to assess the efficacy of dronedarone 400 mg twice daily for the prevention of cardiovascular hospitalization or death from any cause in patients with AF/atrial flutter), 18 in addition to reducing a primary outcome of death or cardiovascular hospitalization.…”
Section: Discussionmentioning
confidence: 87%
“…The general safety of ERC has recently also been corroborated by analyses in large observational data sets. 5 , 6 Based on the inclusion criteria of the EAST-AFNET 4 trial, the majority of patients with new-onset AF are eligible for ERC. 6 The results have started to shift the use of rhythm control therapy from a symptom-driven therapy to a risk-reducing strategy aiming at restoring and maintaining sinus rhythm as the default therapy in patients with recently diagnosed AF and stroke risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…No additional studies were found in the reference lists of previous reviews [17,18]. Finally, a total of 8 studies [8,[10][11][12][19][20][21][22] (1 RCT [8], 2 post hoc analyses of RCTs [11,12], and 5 observational cohorts [10,[19][20][21][22]) were included in this meta-analysis.…”
Section: Study Identification and Selectionmentioning
confidence: 99%